The Torah ark in Renaissance Poland : a Jewish revival of classical antiquity - Rodov, Ilia M. (Jewish and Christian Perspectives Series, 2013)
The volume explores the stone carved shrines for the scrolls of the Mosaic Law from the mid-sixteenth to the mid-seventeenth century synagogues in the former Polish Kingdom. Created on the margin of mainstream art and at a crossroad of diverse cultures, artistic traditions, aesthetic attitudes and languages, these indoor architectural structures have hitherto not been the subject of a monographic study. Revisiting and integrating multiple sources, the author re-evaluates the relationship of the Jewish culture in Renaissance Poland with the medieval Jewish heritage, sepulchral art of the Polish court and nobles, and earlier adaptations of the Christian revival of classical antiquity by Italian Jews. The book uncovers the evolution of artistic patronage, aesthetics, expressions of identities, and emerging visions among a religious minority on the cusp of the modern age.